Preparation of Phase-Pure Perovskite 0.7Pb(Mg1/3Nb2/3)O3-0.3PbTiO3 Ceramics and Effects of Perovskite Phase Purity. Issue 1 (12th February 2023) - Wang, Wuyang; Dai, Fuhong; Fang, Bijun
Abstract: 0.7Pb(Mg1/3 Nb2/3 )O3 -0.3PbTiO3 (PMNT) piezoelectric ceramics were prepared by traditional ceramic processing via B-site oxide mixing route and columbite precursor method using oxides as raw materials, where the influences of MgO purity, whether heat treatment of MgO and synthesis techniques were studied. When using MgO with purity of 98%, the amount of pyrochlore phase in the sintered PMNT ceramics is rather high no matter what synthesis techniques used. Phase-pure perovskite PMNT ceramics can be prepared via the columbite precursor method using 99.99% MgO as raw material after pre-heated at 1200 °C for 4 h. All the PMNT ceramics exhibit rhombohedral perovskite structure with composition approaching the morphotropic phase boundary. The ceramics' density is affected little by pyrochlore impurity, whereas the sintering temperature range is narrow and the 1245 °C sintered phase-pure PMNT ceramics have the largest relative density and compact micro-morphology. The PMNT ceramics present apparent relaxor ferroelectrics characteristic, where the samples with low content of pyrochlore phase or with phase-pure perovskite structure have excellent dielectric property. The samples present easy polarization characteristic, in which the PMNT ceramics with high purity or phase-pure perovskite phase have excellent piezoelectricity.